2014
DOI: 10.1123/jsep.2013-0266
|View full text |Cite
|
Sign up to set email alerts
|

Precompetitive Achievement Goals, Stress Appraisals, Emotions, and Coping Among Athletes

Abstract: Grounded in Lazarus's (1991, 1999, 2000) cognitive-motivational-relational theory of emotions, we tested a model of achievement goals, stress appraisals, emotions, and coping. We predicted that precompetitive achievement goals would be associated with appraisals, appraisals with emotions, and emotions with coping in our model. The mediating effects of emotions among the overall sample of 827 athletes and two stratified random subsamples were also explored. The results of this study support our proposed model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
56
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 39 publications
8
56
2
6
Order By: Relevance
“…These findings were echoed by Isoard-Gautheur et al (2016) who reported that a stronger perceived coach–athlete relationship was associated with mastery-approach goals. There is also evidence that links goals with how an athlete evaluates stress (Nicholls et al, 2014, 2016a). Athletes who adopt mastery-approach goals are more likely to view stressful situations as challenging, whereas athletes who endorse mastery-avoidance or performance-avoidance are more likely to experience threat when in stressful situations (Nicholls et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were echoed by Isoard-Gautheur et al (2016) who reported that a stronger perceived coach–athlete relationship was associated with mastery-approach goals. There is also evidence that links goals with how an athlete evaluates stress (Nicholls et al, 2014, 2016a). Athletes who adopt mastery-approach goals are more likely to view stressful situations as challenging, whereas athletes who endorse mastery-avoidance or performance-avoidance are more likely to experience threat when in stressful situations (Nicholls et al, 2014).…”
mentioning
confidence: 99%
“…There is also evidence that links goals with how an athlete evaluates stress (Nicholls et al, 2014, 2016a). Athletes who adopt mastery-approach goals are more likely to view stressful situations as challenging, whereas athletes who endorse mastery-avoidance or performance-avoidance are more likely to experience threat when in stressful situations (Nicholls et al, 2014). Further, athletes who use goal re-engagement strategies are likely to experience challenge states, whereas goal disengagement strategies are more likely to generate threat appraisals (Nicholls et al, 2016a).…”
mentioning
confidence: 99%
“…While there is an inherent relationship between the key constructs of the CMRT of emotion (Lazarus, ), researchers have essentially focused on one or two constructs (e.g., Nicholls et al., ). Very few studies have explored the overall sequence of the constructs central to the CMRT of emotion (e.g., Nicholls et al., , ; Doron & Gaudreau, ; Doron & Martinent, ). Using structural equation modeling, Nicholls et al.…”
mentioning
confidence: 99%
“…Além disso, a competição pode ser caracterizada como uma situação que envolve ego, novidade, ansiedade, falta de controle e imprevisibilidade, podendo levar a propriedades afetivas negativas 30 . Porém, como o estresse é composto por variáveis muito subjetivas, os resultados podem variar de acordo com a experiência anterior dos sujeitos com eventos competitivos, o tipo de trabalho psicológico que os atletas recebem para conseguir criar estratégias de controle do estresse (coping), qual o nível de cobrança que os jogadores tem para aquela competição analisada, o nível de motivação e outras razões que podem modificar as respostas emocionais associadas ao estresse [31][32][33] . Em conclusão, a carga interna competitiva teve efeito progressivo em função dos três jogos consecutivos, da mesma forma que a percepção subjetiva de esforço, demonstrando que este tipo de competição pode promover uma demanda fisiológica e psicológica que pode refletir no desempenho de jovens escolares que estão inseridos em programas de treinamento sistemá-tico de alguma modalidade esportiva.…”
Section: Conflito De Interessesunclassified